Analysis of Potential Work Hazard Risk in the Development of the Road Project Using the HIRARC and FTA Methods - Manurung, Liza Olivia; Putra, I Nyoman Dita Pahang; Widowati, Elok Dewi (Physical Sciences, Life Science and Engineering, 2025)
Risk refers to a situation with potential loss or the chance of a loss. Every stage in the construction process inevitably carries potential risk hazards that can threaten the safety of workers, the environment, and the surrounding community. Therefore, a study was conducted to analyse possible risks during mobilising heavy equipment and material vehicles, excavation and embankment work, and blasting work in the X Road construction project.  This study employed two methods for risk analysis. The first method involved identifying types of work-related accidents using the HIRARC approach, which included distributing questionnaires to assess each variable's likelihood and severity levels to determine the most significant risk. Then, control measures were applied to the identified risks. After implementing the control measures, a risk reassessment was conducted to assess the level of risk post-control. The identification revealed one dominant variable: heavy equipment overturning from a height. Thus, the analysis continued using the second FTA method to determine the causal factors influencing the risk. The risk was caused by three main factors: human, environmental, and managerial factors, and ten basic events leading to the risk were identified.